Altered Fecal Microbiome and Metabolome in a Mouse Model of Choroidal Neovascularization - Li, Yun; Cai, Yuting; Huang, Qian; Tan, Wei; Li, Bingyan; Zhou, Haixiang; Wang, Zicong; Zou, Jingling; Ding, Chun; Jiang, Bing; Yoshida, Shigeo; Zhou, Yedi (Frontiers in Microbiology, 2021)
Purpose: Choroidal neovascularization (CNV) is the defining feature of neovascular age-related macular degeneration (nAMD). Gut microbiota might be deeply involved in the pathogenesis of nAMD. This study aimed to reveal the roles of the gut microbiome and fecal metabolome in a mouse model of laser-induced CNV. Methods: The feces of C57BL/6J mice with or without laser photocoagulation treatment were collected. Multi-omics analyses, including 16S rRNA gene sequencing and untargeted metabolomics, were conducted to analyze the changes in the gut microbial composition and the fecal metabolomic profiles in CNV mice. Results: The gut microbiota was significantly altered in CNV mice. The abundance of Candidatus_Saccharimonas was significantly upregulated in the feces of CNV mice, while 16 genera, including Prevotellaceae_NK3B31_group, Candidatus_Soleaferrea and Truepera, were significantly more abundant in the controls than in the CNV group. Fecal metabolomics identified 73 altered metabolites (including 52 strongly significantly altered metabolites) in CNV mice compared to control mice. Correlation analysis indicated significant correlations between the altered fecal metabolites and gut microbiota genera, such as Lachnospiraceae_UCG-001 and Candidatus_Saccharimonas. Moreover, KEGG analysis revealed 6 pathways associated with these altered metabolites, such as the ABC transporter, primary bile acid biosynthesis and steroid hormone biosynthesis pathways. Conclusions: The study identified an altered fecal microbiome and metabolome in a CNV mouse model. The altered microbes and metabolites and the involved pathways might be associated with the pathogenesis of nAMD.